A NEW SPECIES DIPLOPYLIDIUM AURANGABADENSIS N. SP. (EUCESTODA : DIPYLIDIIDAE) FROM FELIS DOMESTICUS AT AURANGABAD, INDIA. - SHINDE, G. B.; PAWAR, S. B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Diploylidium aurangabadensis n. sp. collected from Felis domesticus at Aurangabad, differs from all the known species, however it comes closer to D. genettae, D. guinguecolonatum and D. udgirensis in. sp. (described earlier) but it differs from them in many other characters in size, number of rostellar hooks, testes number and position of genital apertures of the worm.